Humanization of the bond between doctor and patient: A look at maternal and child care - Andrade, Maria Clara Pinto; Ferreira, Anna Carla Silva; Araújo, Bruno Henrique Silva; Neta, Francisca Diana Braga; de Santana, Maria Ângela Santos; Fontenele, Maria Isabela Siqueira; Batista, Laura Augusta Freire; Santos, Lara Lis Leite; Santos, Alcione de Oliveira (Seven Editora, 2024)
Humanization consists of the set of techniques and actions that, built within its principles, promotes the quality of relationships between health professionals and patients in which the public, especially maternal and child, is lacking in this aspect in Brazilian hospitals. The purpose of this study is, based on the literature review, to condense information on the process of humanization in health in the maternal-child context in Brazil. The main difficulties encountered in making this theme effective in the context of health are the absence of maternal protagonism in childbirth, introspection of physicians when dealing with the newborn's family and the stressful environment of the Neonatal Intensive Care Unit. The importance of teaching about humanization in the country's universities for the training of human medical professionals in the care of Obstetrics and Neonatology is understood. It is verified that this article concludes that there is a lack of studies regarding the humanization of the doctor-patient relationship in the circumstance of maternal-child health and that, although there are hospitals that encourage the adoption of humanized behaviors in the country, it is still not a unanimous reality in Brazil. DOI:https://doi.org/10.56238/sevened2024.026-024